2004
DOI: 10.1105/tpc.018986
|View full text |Cite
|
Sign up to set email alerts
|

Viral Virulence Protein Suppresses RNA Silencing–Mediated Defense but Upregulates the Role of MicroRNA in Host Gene Expression[W]

Abstract: Small interfering RNAs (siRNAs) and microRNAs (miRNAs) are processed by the ribonuclease Dicer from distinct precursors, double-stranded RNA (dsRNA) and hairpin RNAs, respectively, although either may guide RNA silencing via a similar complex. The siRNA pathway is antiviral, whereas an emerging role for miRNAs is in the control of development. Here, we describe a virulence factor encoded by turnip yellow mosaic virus, p69, which suppresses the siRNA pathway but promotes the miRNA pathway in Arabidopsis thalian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
152
0
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 232 publications
(169 citation statements)
references
References 64 publications
10
152
0
7
Order By: Relevance
“…Helper component-proteinase (HC-Pro), p19, p21, and p69, are unrelated viral suppressors of gene silencing, and they play important roles in the virus response to plant antiviral silencing response (Plisson et al, 2003;Chapman et al, 2004). Several investigations demonstrated that several miRNAs are related the activity of these viral suppressors (Kasschau et al, 2003;Chapman et al, 2004;Chen et al, 2004;Llave, 2004). HC-Pro inhibited the expression level and activity of miR171, and caused miR171-related developmental deficiency (Kasschau et al, 2003).…”
Section: Functions Of Micrornas In Plantsmentioning
confidence: 99%
“…Helper component-proteinase (HC-Pro), p19, p21, and p69, are unrelated viral suppressors of gene silencing, and they play important roles in the virus response to plant antiviral silencing response (Plisson et al, 2003;Chapman et al, 2004). Several investigations demonstrated that several miRNAs are related the activity of these viral suppressors (Kasschau et al, 2003;Chapman et al, 2004;Chen et al, 2004;Llave, 2004). HC-Pro inhibited the expression level and activity of miR171, and caused miR171-related developmental deficiency (Kasschau et al, 2003).…”
Section: Functions Of Micrornas In Plantsmentioning
confidence: 99%
“…Arabidopsis expressing the HCRSV CP transgene shows developmental defects resembling those of mutant lines rdr6-11 and dcl4-2 Many gene-silencing suppressors have been implicated in abnormal plant development by interfering with the miRNA/siRNA pathways (Chapman et al, 2004;Chen et al, 2004;Dunoyer et al, 2004;Zhang et al, 2006). To test whether the carmovirus HCRSV CP would affect normal plant development, lines CP6 and DCP20 were used for phenotypic analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Crossings between CP or DCP and L1, A or G6A lines were carried out as described previously (Chen et al, 2004). After crossing, the introduced sequences and the effects of CP and DCP on the accumulation of transgene and amplicon-specific mRNA and siRNAs were detected by Northern blotting.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations